2022
DOI: 10.1080/09593969.2022.2158119
|View full text |Cite
|
Sign up to set email alerts
|

Changes in market organisation due to exogenous shocks – the case of the transformation of the Swedish fashion industry caused by the COVID-19 pandemic

Abstract: This study aims to provide insights into the transformation of retail caused by the COVID-19 pandemic, using the Swedish fashion industry as an example. In an institutional perspective, combined with Actor-network theory, both new actors and the changing role of existing ones were identified as influencing how the market was organised. An empirical field study of the Swedish fashion industry has illustrated the changes caused to retail by the outbreak of COVID-19, and the subsequent actions taken to limit its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Despite these opportunities, the authors also discussed the challenges of digital transformation, such as data privacy and security concerns, the digital divide, the need for upskilling and reskilling, and potential job loss due to automation. The study by Wulff (2022) emphasised the importance of adaptability and resilience, particularly in the Swedish fashion industry, in the face of exogenous shocks and suggested that embracing digital transformation and sustainable practices can help businesses navigate such challenges more effectively. Companies that could quickly respond to the changing market conditions, pivot their business models, and embrace digitalisation were better positioned to weather the challenges posed by the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite these opportunities, the authors also discussed the challenges of digital transformation, such as data privacy and security concerns, the digital divide, the need for upskilling and reskilling, and potential job loss due to automation. The study by Wulff (2022) emphasised the importance of adaptability and resilience, particularly in the Swedish fashion industry, in the face of exogenous shocks and suggested that embracing digital transformation and sustainable practices can help businesses navigate such challenges more effectively. Companies that could quickly respond to the changing market conditions, pivot their business models, and embrace digitalisation were better positioned to weather the challenges posed by the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Retailers are advised to use a shared e-commerce platform with other companies to pool resources for storage and delivery during the pandemic (Wulff, 2022). Retailers can pool resources and cut expenses whilst still maintaining their own distinctive branding and consumer experience by utilising a shared platform (Sodhi and Tang, 2021).…”
Section: Leverage E-commerce Capabilitiesmentioning
confidence: 99%
“…Seeking banks, governments, or any other organisation for financial assistance Governments and banks have started assistance initiatives to aid businesses impacted by the pandemic. Retailers can assess these programs to understand those that are relevant and apply for financial aid (Wulff, 2022). Therefore, retailers should prepare detailed financial statements that are a true reflection of their actual financial position (H€ anninen et al, 2021).…”
Section: Rethinking Distribution and Inventory Strategiesmentioning
confidence: 99%
“…As the world undergoes socio-economic changes, consumers are changing their approach to online shopping. Buyers are less and less concerned about mismatches in products ordered online, due to the increasing return options currently offered by the vast majority of online stores (Wulff, 2022). The apparel and footwear market is reaching its highest point on the international trade front.…”
Section: Figure 4 E-commerce Market Penetration Rate In Selected Coun...mentioning
confidence: 99%